6.91 Problems 9001 to 9100

Table 6.181: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

9001

\[ {}c y^{\prime } = y \]

9002

\[ {}c y^{\prime } = b y \]

9003

\[ {}c y^{\prime } = a x +b y^{2} \]

9004

\[ {}c y^{\prime } = \frac {a x +b y^{2}}{r} \]

9005

\[ {}c y^{\prime } = \frac {a x +b y^{2}}{r x} \]

9006

\[ {}c y^{\prime } = \frac {a x +b y^{2}}{r \,x^{2}} \]

9007

\[ {}c y^{\prime } = \frac {a x +b y^{2}}{y} \]

9008

\[ {}a \sin \left (x \right ) y x y^{\prime } = 0 \]

9009

\[ {}f \left (x \right ) \sin \left (x \right ) y x y^{\prime } \pi = 0 \]

9010

\[ {}y^{\prime } = \sin \left (x \right )+y \]

9011

\[ {}y^{\prime } = \sin \left (x \right )+y^{2} \]

9012

\[ {}y^{\prime } = \cos \left (x \right )+\frac {y}{x} \]

9013

\[ {}y^{\prime } = \cos \left (x \right )+\frac {y^{2}}{x} \]

9014

\[ {}y^{\prime } = x +y+b y^{2} \]

9015

\[ {}x y^{\prime } = 0 \]

9016

\[ {}5 y^{\prime } = 0 \]

9017

\[ {}{\mathrm e} y^{\prime } = 0 \]

9018

\[ {}\pi y^{\prime } = 0 \]

9019

\[ {}\sin \left (x \right ) y^{\prime } = 0 \]

9020

\[ {}f \left (x \right ) y^{\prime } = 0 \]

9021

\[ {}x y^{\prime } = 1 \]

9022

\[ {}x y^{\prime } = \sin \left (x \right ) \]

9023

\[ {}\left (x -1\right ) y^{\prime } = 0 \]

9024

\[ {}y y^{\prime } = 0 \]

9025

\[ {}x y y^{\prime } = 0 \]

9026

\[ {}x y \sin \left (x \right ) y^{\prime } = 0 \]

9027

\[ {}\pi y \sin \left (x \right ) y^{\prime } = 0 \]

9028

\[ {}x \sin \left (x \right ) y^{\prime } = 0 \]

9029

\[ {}x \sin \left (x \right ) {y^{\prime }}^{2} = 0 \]

9030

\[ {}y {y^{\prime }}^{2} = 0 \]

9031

\[ {}{y^{\prime }}^{n} = 0 \]

9032

\[ {}x {y^{\prime }}^{n} = 0 \]

9033

\[ {}{y^{\prime }}^{2} = x \]

9034

\[ {}{y^{\prime }}^{2} = x +y \]

9035

\[ {}{y^{\prime }}^{2} = \frac {y}{x} \]

9036

\[ {}{y^{\prime }}^{2} = \frac {y^{2}}{x} \]

9037

\[ {}{y^{\prime }}^{2} = \frac {y^{3}}{x} \]

9038

\[ {}{y^{\prime }}^{3} = \frac {y^{2}}{x} \]

9039

\[ {}{y^{\prime }}^{2} = \frac {1}{x y} \]

9040

\[ {}{y^{\prime }}^{2} = \frac {1}{x y^{3}} \]

9041

\[ {}{y^{\prime }}^{2} = \frac {1}{x^{2} y^{3}} \]

9042

\[ {}{y^{\prime }}^{4} = \frac {1}{x y^{3}} \]

9043

\[ {}{y^{\prime }}^{2} = \frac {1}{y^{4} x^{3}} \]

9044

\[ {}y^{\prime } = \sqrt {1+6 x +y} \]

9045

\[ {}y^{\prime } = \left (1+6 x +y\right )^{{1}/{3}} \]

9046

\[ {}y^{\prime } = \left (1+6 x +y\right )^{{1}/{4}} \]

9047

\[ {}y^{\prime } = \left (a +b x +y\right )^{4} \]

9048

\[ {}y^{\prime } = \left (\pi +x +7 y\right )^{{7}/{2}} \]

9049

\[ {}y^{\prime } = \left (a +b x +c y\right )^{6} \]

9050

\[ {}y^{\prime } = {\mathrm e}^{x +y} \]

9051

\[ {}y^{\prime } = 10+{\mathrm e}^{x +y} \]

9052

\[ {}y^{\prime } = 10 \,{\mathrm e}^{x +y}+x^{2} \]

9053

\[ {}y^{\prime } = x \,{\mathrm e}^{x +y}+\sin \left (x \right ) \]

9054

\[ {}y^{\prime } = 5 \,{\mathrm e}^{x^{2}+20 y}+\sin \left (x \right ) \]

9055

\[ {}[x^{\prime }\left (t \right )+y^{\prime }\left (t \right )-x \left (t \right ) = y \left (t \right )+t, x^{\prime }\left (t \right )+y^{\prime }\left (t \right ) = 2 x \left (t \right )+3 y \left (t \right )+{\mathrm e}^{t}] \]

9056

\[ {}[2 x^{\prime }\left (t \right )+y^{\prime }\left (t \right )-x \left (t \right ) = y \left (t \right )+t, x^{\prime }\left (t \right )+y^{\prime }\left (t \right ) = 2 x \left (t \right )+3 y \left (t \right )+{\mathrm e}^{t}] \]

9057

\[ {}[x^{\prime }\left (t \right )+y^{\prime }\left (t \right )-x \left (t \right ) = y \left (t \right )+t +\sin \left (t \right )+\cos \left (t \right ), x^{\prime }\left (t \right )+y^{\prime }\left (t \right ) = 2 x \left (t \right )+3 y \left (t \right )+{\mathrm e}^{t}] \]

9058

\[ {}t y^{\prime }+y = t \]

9059

\[ {}y^{\prime }-t y = 0 \]

9060

\[ {}t y^{\prime }+y = 0 \]

9061

\[ {}t y^{\prime }+y = 0 \]

9062

\[ {}t y^{\prime }+y = 0 \]

9063

\[ {}t y^{\prime }+y = 0 \]

9064

\[ {}t y^{\prime }+y = 0 \]

9065

\[ {}t y^{\prime }+y = \sin \left (t \right ) \]

9066

\[ {}t y^{\prime }+y = t \]

9067

\[ {}t y^{\prime }+y = t \]

9068

\[ {}y^{\prime }+t^{2} y = 0 \]

9069

\[ {}\left (a t +1\right ) y^{\prime }+y = t \]

9070

\[ {}y^{\prime }+\left (a t +b t \right ) y = 0 \]

9071

\[ {}y^{\prime }+\left (a t +b t \right ) y = 0 \]

9072

\[ {}y^{\prime \prime } = 0 \]

9073

\[ {}{y^{\prime \prime }}^{2} = 0 \]

9074

\[ {}{y^{\prime \prime }}^{n} = 0 \]

9075

\[ {}a y^{\prime \prime } = 0 \]

9076

\[ {}a {y^{\prime \prime }}^{2} = 0 \]

9077

\[ {}a {y^{\prime \prime }}^{n} = 0 \]

9078

\[ {}y^{\prime \prime } = 1 \]

9079

\[ {}{y^{\prime \prime }}^{2} = 1 \]

9080

\[ {}y^{\prime \prime } = x \]

9081

\[ {}{y^{\prime \prime }}^{2} = x \]

9082

\[ {}{y^{\prime \prime }}^{3} = 0 \]

9083

\[ {}y^{\prime \prime }+y^{\prime } = 0 \]

9084

\[ {}{y^{\prime \prime }}^{2}+y^{\prime } = 0 \]

9085

\[ {}y^{\prime \prime }+{y^{\prime }}^{2} = 0 \]

9086

\[ {}y^{\prime \prime }+y^{\prime } = 1 \]

9087

\[ {}{y^{\prime \prime }}^{2}+y^{\prime } = 1 \]

9088

\[ {}y^{\prime \prime }+{y^{\prime }}^{2} = 1 \]

9089

\[ {}y^{\prime \prime }+y^{\prime } = x \]

9090

\[ {}{y^{\prime \prime }}^{2}+y^{\prime } = x \]

9091

\[ {}y^{\prime \prime }+{y^{\prime }}^{2} = x \]

9092

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

9093

\[ {}{y^{\prime \prime }}^{2}+y^{\prime }+y = 0 \]

9094

\[ {}y^{\prime \prime }+{y^{\prime }}^{2}+y = 0 \]

9095

\[ {}y^{\prime \prime }+y^{\prime }+y = 1 \]

9096

\[ {}y^{\prime \prime }+y^{\prime }+y = x \]

9097

\[ {}y^{\prime \prime }+y^{\prime }+y = 1+x \]

9098

\[ {}y^{\prime \prime }+y^{\prime }+y = x^{2}+x +1 \]

9099

\[ {}y^{\prime \prime }+y^{\prime }+y = x^{3}+x^{2}+x +1 \]

9100

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \]